Changes in genetic variant results over time in pediatric cardiomyopathy and electrophysiology. Issue 1 (24th July 2020) - Cherny, Sara; Olson, Rachael; Chiodo, Kathryn; Balmert, Lauren C.; Webster, Gregory
Abstract: Genetic testing for cardiac disorders continues to change. Our objective was to assess trends in variant classification in pediatric arrhythmia and cardiomyopathy. We conducted a retrospective review of patients tested for genetic arrhythmia and cardiomyopathy disorders from 2006–2017. Variants were classified by CLIA laboratories. Trends were assessed by the Spearman correlation. There were 914 variants in 583 patients from 337 families. The total number of tests ordered increased over time, accelerating after 2012. There was a strong positive correlation between the average number of genes tested per panel and year of testing ( r  = .97, p  < .001) and a weak correlation between the year and a decrease in the percentage of clinically actionable variants ( r  = −.20, p  = .005). By 2011, VUS represented >50% of variants reported on panels. Over 12 years, 203 genes were interrogated; one or more variants were reported in 91 of 203 genes (45%). 32% of patients had at least one clinically actionable variant; 28% had at least one VUS. Reclassification is an important long‐term issue, with 21.5% variants changing clinical interpretation. We observed an increase over time in three areas: total number of tests ordered, average number of genes/panel, and percentage of VUS. Providers may need to interpret results from 90 + genes, and ongoing education is critical. Due to their specific training in test result interpretation, we recommend the inclusion of a genetic counselor in pediatric electrophysiology and cardiomyopathy teams.